A state space distribution approach based on system behaviour. (26th July 2019) - Bensetira, Imene; Saidouni, Djamel Eddine; Alamin, Mahfud Al-la
In this paper, we propose a novel approach to deal with the state space explosion problem occurring in model checking. We propose an offline algorithm for distributed state space construction. That is carried out by reviewing the behaviour of the constructed system and redistributing the state space according to the accumulated information about the optimal considered behaviour. Therefore, the distribution will be guided by the system's behaviour. The proposed policy maintains the spatial-time balance. The simulation and implementation of our system are based on a multi-agent technique which fits very well the development of distributed systems. The experimental measures performed on a cluster of machines have shown very promising results for both workload balance and communication overhead.